The Effect of Depth Jump Training on Improving Lower-Body Explosive Strength in Players of the 08 Junior Volleyball Club in North Bengkulu - Setiadiansyah Setiadiansyah; Dody Ertanto; Asnawati Asnawati (Educative Sportive, 2026)
This study aims to determine the effect of depth jump training on increasing the leg muscle explosive power of volleyball players at Club Junior 08 Bengkulu Utara. A total sampling method was used to determine the number of respondents, resulting in 15 respondents who are volleyball athletes from Club Junior 08 Bengkulu Utara. This experimental research employed a One-Group Pretest-Posttest design, which is a pre-experimental design that involves a pre-test (test before treatment) and a post-test (test after treatment) within a single group. Data collection was carried out using test scores. The data analysis techniques used were descriptive analysis and the t-test.The results of this study indicate that there is an effect of depth jumps on increasing the leg muscle explosive power of Club Junior 08 Bengkulu Utara volleyball players, with a calculated t-value ($t_{count}$) of 3.534, while the t-table ($t_{table}$) is 2.14 at a significance level of $α = 0.05$ and degrees of freedom ($df$) = 15.